Methods of regional forecasting - Kocziszky, György (NTU "KhPI", 2009)
The need for seeing into the future is probably as old as mankind. In spite of notorious experiments, methodically well-founded economic-social forecasts have only been made since the middle of the 20th century. The objective of forecasts is to get to know the expected medium and long-term tendencies (collectively: vision), quantify them as far as possible, and incorporate them into plans. It is important to emphasise that forecasts are designed to describe the situations that can be expected and not to collect ’dreams’. Forecasts at the same time are not magic wands which can draw exclusively positive tendencies. Therefore forecasts have the essential task of taking expected negative tendencies into account.

Потребность прогнозирования будущего столь же стара как человечество. Несмотря на печально известные эксперименты, систематически экономическо-социальные предсказания были сделаны начиная с середины 20-го столетия. Задача предсказаний - необходимо знать длительную тенденцию изменения возможностей, которая и должна быть в основе планирования. В то же время прогнозы – это не волшебная палочка, которая может представлять исключительно положительную тенденцию. Поэтому предсказания имеют существенную задачу уменьшить возможное наличие негативных тенденций в экономике.